THE USE OF DIGITAL CINEMA IN THE PROMOTION OF GENDER EQUALITY IN SCHOOL - Fernanda de Carvalho Azevedo Mello; Janderlan Alexandre de Araujo; Andréa Carla Mendonça de Souza Paiva; Maria Grazia Cribari Cardoso (Política e Gestão Educacional, 2017)
This work aims to present the use of digital cinema to discuss diversity and gender inequality in society, based on debates among high school students. As a result of an extension project of the Universidade Federal Rural de Pernambuco (UFRPE), titled Cine debate: gender and race equality in school, the action consisted of films exhibition on gender among students of a known state public school called Professor Cândido Duarte. Two criteria were adopted for the selection of the cinematography: Brazilian short films that covered the project themes, such as gender differences (in their diverse thematic lines). After the broadcast of the films, the debate was encouraged among the students. Finally, it was requested the evaluation of these films from a questionnaire with open and closed questions (RICHARDSON, 1999) that asked about the cinematographic work and its relation with the daily life. In addition to that, it was requested some basic information, such as name, age, sex, color, religion and school series. The analysis of the questionnaires pointed out the relevance of the digital cinema as a communication tool that can be used to reflect on gender and work condition between men and women in society and family, increasing the learning and encouraging the debate.